KEJADIAN LUAR BIASA KERACUNAN “CUMI-CUMIAN” DI SEKOLAH DASAR NEGERI 1 TRASAN BANDONGAN KABUPATEN MAGELANG - Nasir Ahmad; Adi Isworo; Citra Indriani (Universitas Jenderal Achmad Yani Yogyakarta, 2018)
Background: On May 4th, 2016, at 12:30 district surveillance officer of Magelang Health Department received reports from Public Health Center of Bandongan about 21 students of SDN 1 Trasan who suffered from the same food-poisoning symptoms. Objective: Investigation was carried out to identify the source, how it spread and how to control it. Methods: This study used descriptive analytic and mapping the cases distribution location. The case was people experiencing symptoms of dizziness or abdominal pain or nausea or vomiting. Data analysis was done by using bivariate analysis. Data collection were done through interviews, observations and laboratory tests on the food samples. Results: The case was 50 students (from 1-6 grade students). The perceived symptoms were dizziness (77%), nausea (42%), abdominal pain (40%) and vomiting (8%). Attack rate found ranged from 14.3% to 60% with the highest Attack rate found on class three (60%). The incubation period of 15-240 minutes (mean 72.3 minutes). Calamari like positive Bacillus cereus and Rhodamine-B 10 mg/kg. Conclusion: The outbreak of food poisoning because calamari like contaminated Bacillus cereus. We suggested the school committee to provide the socialization of harmful food for the students. The teachers should restrict the permission for the food vendor to sell at school. Keywords: Bacillus cereus, , Food Poisoning, Outbreak, Rhodamine B, School Food